Water imagery and the power and presence of God in the Gospel of John - Brown, Sherri (2015)
This article explores the role of symbolism in the gospel narrative in general and the suggestion that symbolism lies at the core of the theology of the Gospel of John. In particular, the Fourth Evangelist’s use of water imagery is deeply rooted in his Jewish scripture, where control of the waters is the prerogative of God alone. Johannine use of water symbolism is therefore discussed in terms of creation, the Exodus, human longing for God, and the manifestation of God known as “theophany.” By way of application, the dialogue between Jesus and the Samaritan woman at the well about the presence of God in living water in John 4 and the sign of the power of God seen through Jesus walking on the water of the Sea of Galilee in John 6 are interpreted for their capacity to reveal the power and presence of God acting in reality through the mission and ministry of Jesus the Christ and Son of God.
Keywords: Water; Symbolism; Samaritan Woman; Gospel of John; God